Early outcome of surgical intervention in subaxial cervical spine injuries - S., Vignesh; B., Pradeep; D., Balasubramanian (International Journal of Research in Medical Sciences, 2018)
Background: Sub-axial cervical spine includes the C3 through C7 segments, a very mobile area of the spine with potential for devastating injuries as a result of instability and risk of spinal cord injury. Goal of treatment is to stabilize the spine and decompress when necessary, in order to promote the optimal environment for recovery. Methods: This is a retrospective study of 40 patients with sub-axial cervical spine injury who underwent surgery in this institute from January 2016 to March 2017. Results: Most of the patients were young males with road traffic accident. They underwent cerival traction for reducing translation and surgical management, mostly anterior procedures and in some cases posterior stabilisation. Conclusions: Most of the subaxial spine injuries can be treated by anterior procedures. Preoperative neurological status is an important predictor in postoperative neurological improvement.